A preparation process of high-purity refined activated carbon
By using the synergistic action of eucalyptus wood chips and specific cocatalysts, high purity refined activated carbon was prepared, which solved the problems of low specific surface area and high ash content of wood biomass activated carbon, and achieved efficient preparation and excellent adsorption performance of activated carbon.
Patent Information
- Application Number
- CN202411098749.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-12
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2044-08-12
AI Technical Summary
The specific surface area of woody biomass activated carbon is generally low, and the residual unreacted activator or its decomposition products increase the ash content, resulting in a decrease in the purity of activated carbon and affecting its adsorption performance.
Eucalyptus wood chips are used as raw materials, and through the steps of impregnation of phosphoric acid solution, ultrasonic dispersion, reflux and stirring, combined with the mixture of diethoxyethyl succinate, deionized water, and anhydrous ethanol, cocatalyst A and cocatalyst B are added to perform carbonization and activation treatment to reduce the ash content of activated carbon.
It effectively reduces the ash content of activated carbon, improves its purity and specific surface area, enhances adsorption performance, and improves the quality of activated carbon.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of activated carbon, and in particular relates to a preparation process of high-purity refined activated carbon. Background Art
[0002] Industrial activated carbon is mainly prepared by carbonization and activation using coal, asphalt, biomass, etc. as raw materials. However, the production process of coal-based activated carbon has problems such as environmental pollution and non-renewable raw materials, and is gradually replaced by wood biomass activated carbon. Woody biomass is the most abundant renewable biomass resource on the earth, including wood (such as eucalyptus, beech, fir and poplar) and agricultural and forestry waste (such as corn stalks, wheat stalks, sorghum stalks and rice husks). It has the characteristics of wide sources, universality and cheap accessibility, and is now widely used as the basic raw material for the preparation of activated carbon. However, woody biomass has the characteristics of tight lignin structure, which makes it difficult for the activator to fully activate it, resulting in a generally low specific surface area of the activated carbon obtained by direct activation. At the same time, the unreacted activator or its decomposition products remain, increasing the ash content, resulting in a decrease in the purity of the obtained activated carbon, affecting its adsorption performance. Summary of the invention
[0003] The object of the present invention is to provide a preparation process of high-purity refined activated carbon, which is used to reduce the ash content of the activated carbon and improve its purity and quality.
[0004] The purpose of the present invention can be achieved through the following technical solutions:
[0005] A preparation process of high-purity refined activated carbon comprises the following steps:
[0006] S1. Grind eucalyptus sawdust, ball-mill, immerse in phosphoric acid solution, ultrasonically disperse for 20-30 min, and dry at 120-130° C. for 10-20 min to obtain material A;
[0007] S2, taking the material A, diethoxyethyl succinate, deionized water and anhydrous ethanol, mixing them, refluxing and stirring at 110° C. for 6-8 hours, filtering with suction, washing the filter cake, and vacuum drying to obtain material B;
[0008] S3, take co-catalyst A, co-catalyst B, and deionized water, mix, stir for 20-30 minutes, add the material B, ultrasonically disperse for 30-40 minutes, vacuum dry to constant weight, then carbonize, activate, cool, wash to neutrality, and vacuum dry at 80° C. for 10 hours to obtain the high-purity refined activated carbon.
[0009] As a preferred technical solution of the present invention, in step S1, the dosage ratio of the eucalyptus sawdust to the phosphoric acid solution is 10-12 g: 70-80 mL.
[0010] As a preferred technical solution of the present invention, the mass fraction of phosphoric acid in the phosphoric acid solution is 55%.
[0011] As a preferred technical solution of the present invention, in step S2, the dosage ratio of material A, diethoxyethyl succinate, deionized water and anhydrous ethanol is 4-5g:10g:40mL:10mL.
[0012] As a preferred technical solution of the present invention, in step S3, the mass ratio of the co-catalyst A, co-catalyst B, deionized water and material B is 0.1-0.15:0.04-0.05:50:10.
[0013] As a preferred technical solution of the present invention, the co-catalyst A is composed of ammonium carbonate and ammonium bisulfite in a mass ratio of 4-5:0.4-0.5.
[0014] As a preferred technical solution of the present invention, the preparation of the co-catalyst B comprises the following steps:
[0015] S31, sodium hydride and tetrahydrofuran were mixed, p-hydroxybenzaldehyde was added, the mixture was refluxed at room temperature under nitrogen atmosphere with stirring for 5-7h, hexachlorocyclotriphosphazene was added, the mixture was refluxed at 62-67°C with stirring for 30-40h, filtered, and the liquid phase was taken to obtain material C;
[0016] S32, take the material C, potassium permanganate, sodium hydroxide, and deionized water, mix them, reflux and stir at 62-67° C. for 30-40 hours, filter, take the liquid phase to adjust the pH to 4-5, filter, take the solid phase and vacuum dry it to constant weight to obtain the co-catalyst B.
[0017] As a preferred technical solution of the present invention, in step S31, the mass ratio of sodium hydride, tetrahydrofuran, p-hydroxybenzaldehyde and hexachlorocyclotriphosphazene is 3-3.3:80-90:9-10:3-4.
[0018] As a preferred technical solution of the present invention, in step S32, the mass ratio of material C, potassium permanganate, sodium hydroxide and deionized water is 7-8:8-10:2-2.2:300-400.
[0019] As a preferred technical solution of the present invention, the carbonization refers to heating the temperature to 400-450°C at a heating rate of 3°C / min in a nitrogen atmosphere and keeping the temperature for 2-3h.
[0020] As a preferred technical solution of the present invention, the activation refers to heating the temperature to 500-600°C at a heating rate of 10°C / min in a nitrogen atmosphere and keeping the temperature for 2-3h.
[0021] Beneficial effects of the present invention:
[0022] The invention discloses a preparation process of high-purity refined activated carbon. Eucalyptus with low ash content is selected as coal. The synergistic effect of the co-catalyst containing nitrogen, phosphorus, sulfur and carboxyl is introduced in the carbonization process to effectively reduce the ash content of the activated carbon and improve the purity of the activated carbon. DETAILED DESCRIPTION
[0023] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.
[0024] Example 1
[0025] A preparation process of high-purity refined activated carbon comprises the following steps:
[0026] S1. Crush eucalyptus sawdust, ball-mill, immerse in phosphoric acid solution, ultrasonically disperse for 20 minutes, and dry at 120° C. for 10 minutes to obtain material A; the ratio of eucalyptus sawdust to phosphoric acid solution is 10 g:70 mL; the mass fraction of phosphoric acid in the phosphoric acid solution is 55%;
[0027] S2, taking the material A, diethoxyethyl succinate, deionized water, and anhydrous ethanol, mixing them, refluxing and stirring at 110° C. for 6 hours, filtering, washing the filter cake, and vacuum drying to obtain material B; the amount ratio of the material A, diethoxyethyl succinate, deionized water, and anhydrous ethanol is 4g:10g:40mL:10mL;
[0028] S3, take the promoter A, the promoter B, and the deionized water, mix them, stir for 20 minutes, add the material B, ultrasonically disperse for 30 minutes, vacuum dry to constant weight, then carbonize, activate, cool, wash to neutrality, and vacuum dry at 80°C for 10 hours to obtain the high-purity refined activated carbon; the mass ratio of the promoter A, the promoter B, the deionized water, and the material B is 0.1:0.04:50:10;
[0029] The carbonization refers to heating the temperature to 400°C at a heating rate of 3°C / min in a nitrogen atmosphere and keeping the temperature for 2 hours; the activation refers to heating the temperature to 500°C at a heating rate of 10°C / min in a nitrogen atmosphere and keeping the temperature for 2 hours;
[0030] The co-catalyst A is composed of ammonium carbonate and ammonium bisulfite in a mass ratio of 4:0.4.
[0031] The preparation of the co-catalyst B comprises the following steps:
[0032] S31, mix sodium hydride and tetrahydrofuran, add p-hydroxybenzaldehyde, reflux and stir at room temperature for 5 hours in a nitrogen atmosphere, add hexachlorocyclotriphosphazene, reflux and stir at 62° C. for 30 hours, filter, and take the liquid phase to obtain material C; the mass ratio of the sodium hydride, tetrahydrofuran, p-hydroxybenzaldehyde, and hexachlorocyclotriphosphazene is 3:80:9:3;
[0033] S32, take the material C, potassium permanganate, sodium hydroxide, and deionized water, mix them, reflux with stirring at 62° C. for 30 hours, filter, take the liquid phase to adjust the pH to 4, filter, take the solid phase and vacuum dry to constant weight to obtain the co-catalyst B; the mass ratio of the material C, potassium permanganate, sodium hydroxide, and deionized water is 7:8:2:300.
[0034] Example 2
[0035] A preparation process of high-purity refined activated carbon comprises the following steps:
[0036] S1. Crush eucalyptus sawdust, ball-mill, immerse in phosphoric acid solution, ultrasonically disperse for 25 minutes, and dry at 125° C. for 15 minutes to obtain material A; the ratio of eucalyptus sawdust to phosphoric acid solution is 11 g:75 mL; the mass fraction of phosphoric acid in the phosphoric acid solution is 55%;
[0037] S2, taking the material A, diethoxyethyl succinate, deionized water, and anhydrous ethanol, mixing, reflux stirring at 110° C. for 7 hours, filtering, washing the filter cake, and vacuum drying to obtain material B; the amount ratio of the material A, diethoxyethyl succinate, deionized water, and anhydrous ethanol is 4.5g:10g:40mL:10mL;
[0038] S3, take the promoter A, the promoter B, and the deionized water, mix them, stir for 25 minutes, add the material B, ultrasonically disperse for 35 minutes, vacuum dry to constant weight, then carbonize, activate, cool, wash to neutrality, and vacuum dry at 80°C for 10 hours to obtain the high-purity refined activated carbon; the mass ratio of the promoter A, the promoter B, the deionized water, and the material B is 0.13:0.045:50:10;
[0039] The carbonization refers to heating the temperature to 425°C at a heating rate of 3°C / min in a nitrogen atmosphere and keeping the temperature for 2.5 hours; the activation refers to heating the temperature to 550°C at a heating rate of 10°C / min in a nitrogen atmosphere and keeping the temperature for 2.5 hours;
[0040] The co-catalyst A is composed of ammonium carbonate and ammonium bisulfite in a mass ratio of 4.5:0.45.
[0041] The preparation of the co-catalyst B comprises the following steps:
[0042] S31, mix sodium hydride and tetrahydrofuran, add p-hydroxybenzaldehyde, reflux and stir at room temperature in a nitrogen atmosphere for 6 hours, add hexachlorocyclotriphosphazene, reflux and stir at 64°C for 35 hours, filter, and take the liquid phase to obtain material C; the mass ratio of the sodium hydride, tetrahydrofuran, p-hydroxybenzaldehyde and hexachlorocyclotriphosphazene is 3.2:85:9.5:3.5;
[0043] S32. Mix the material C, potassium permanganate, sodium hydroxide and deionized water, reflux with stirring at 65°C for 35 hours, filter with suction, adjust the pH of the liquid phase to 4.5, filter, and vacuum dry the solid phase to constant weight to obtain the co-catalyst B; the mass ratio of the material C, potassium permanganate, sodium hydroxide and deionized water is 7.5:9:2.1:350.
[0044] Example 3
[0045] A preparation process of high-purity refined activated carbon comprises the following steps:
[0046] S1. Crush eucalyptus sawdust, ball-mill, immerse in phosphoric acid solution, ultrasonically disperse for 30 minutes, and dry at 130° C. for 20 minutes to obtain material A; the ratio of eucalyptus sawdust to phosphoric acid solution is 12 g: 80 mL; the mass fraction of phosphoric acid in the phosphoric acid solution is 55%;
[0047] S2, taking the material A, diethoxyethyl succinate, deionized water, and anhydrous ethanol, mixing them, refluxing and stirring at 110° C. for 8 h, filtering, washing the filter cake, and vacuum drying to obtain material B; the amount ratio of the material A, diethoxyethyl succinate, deionized water, and anhydrous ethanol is 5g:10g:40mL:10mL;
[0048] S3, take the promoter A, the promoter B, and the deionized water, mix them, stir for 30 minutes, add the material B, ultrasonically disperse for 40 minutes, vacuum dry to constant weight, then carbonize, activate, cool, wash to neutrality, and vacuum dry at 80°C for 10 hours to obtain the high-purity refined activated carbon; the mass ratio of the promoter A, the promoter B, the deionized water, and the material B is 0.15:0.05:50:10;
[0049] The carbonization refers to heating the temperature to 450°C at a heating rate of 3°C / min in a nitrogen atmosphere and keeping the temperature for 3 hours; the activation refers to heating the temperature to 600°C at a heating rate of 10°C / min in a nitrogen atmosphere and keeping the temperature for 3 hours;
[0050] The co-catalyst A is composed of ammonium carbonate and ammonium bisulfite in a mass ratio of 5:0.5.
[0051] The preparation of the co-catalyst B comprises the following steps:
[0052] S31, sodium hydride and tetrahydrofuran are mixed, p-hydroxybenzaldehyde is added, the mixture is refluxed at room temperature under nitrogen atmosphere for 7 hours, hexachlorocyclotriphosphazene is added, the mixture is refluxed at 67° C. for 40 hours, filtered, and the liquid phase is taken to obtain material C; the mass ratio of the sodium hydride, tetrahydrofuran, p-hydroxybenzaldehyde, and hexachlorocyclotriphosphazene is 3.3:90:10:4;
[0053] S32, take the material C, potassium permanganate, sodium hydroxide, and deionized water, mix them, reflux with stirring at 67°C for 40 hours, filter, take the liquid phase to adjust the pH to 5, filter, take the solid phase and vacuum dry to constant weight to obtain the co-catalyst B; the mass ratio of the material C, potassium permanganate, sodium hydroxide, and deionized water is 8:10:2.2:400.
[0054] Comparative Example 1
[0055] The difference from Example 3 is that the co-catalyst A only includes ammonium carbonate.
[0056] Comparative Example 2
[0057] The difference from Example 3 is that the co-catalyst A only includes ammonium bisulfite.
[0058] Comparative Example 3
[0059] The difference from Example 3 is that only the co-catalyst A is added in step S3.
[0060] Comparative Example 4
[0061] The difference from Example 3 is that only the co-catalyst B is added in step S3.
[0062] Comparative Example 5
[0063] The difference from Example 3 is that the preparation of the co-catalyst B comprises the following steps:
[0064] S31, sodium hydride and tetrahydrofuran are mixed, p-hydroxybenzaldehyde is added, the mixture is refluxed at room temperature under nitrogen atmosphere for 7 hours, hexachlorocyclotriphosphazene is added, the mixture is refluxed at 67° C. for 40 hours, filtered, and the liquid phase is taken to obtain material C; the mass ratio of the sodium hydride, tetrahydrofuran, p-hydroxybenzaldehyde, and hexachlorocyclotriphosphazene is 3.3:90:10:4;
[0065] S32, vacuum drying the material C to a constant weight to obtain the co-catalyst B.
[0066] Performance Testing
[0067] The activated carbons prepared in Examples 1-3 and Comparative Examples 1-5 were tested for specific surface area, iodine value, suberan value and ash content. The test results are shown in Table 1 below.
[0068] Table 1
[0069] <![CDATA[Specific surface area (m 2 / g)]]> Iodine value (mg / g) Aran value (mL / 0.1g) Ash content (%) Example 1 1388 1458 15 1.04 Example 2 1394 1473 18 0.87 Example 3 1391 1469 17 0.95 Comparative Example 1 1104 1247 14 1.76 Comparative Example 2 1092 1134 13 2.31 Comparative Example 3 943 897 8 4.74 Comparative Example 4 938 874 7 4.97 Comparative Example 5 1014 1032 10 3.24
[0070] As can be seen from Table 1, the activated carbon prepared in Examples 1-3 of the present application has high purity, low ash content, good specific surface area and adsorption performance, and improves the quality of the activated carbon; the present application selects eucalyptus with low ash content as coal quality, and introduces the synergistic effect of nitrogen, phosphorus, sulfur and carboxyl-containing co-catalysts during the carbonization process to effectively reduce the ash content of the activated carbon and improve the purity of the activated carbon.
[0071] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A process for preparing high-purity refined activated carbon, characterized in that: The following steps are involved: S1. Grind eucalyptus sawdust, ball-mill, immerse in phosphoric acid solution, ultrasonically disperse for 20-30 min, and dry at 120-130° C. for 10-20 min to obtain material A; S2, taking the material A, diethoxyethyl succinate, deionized water and anhydrous ethanol, mixing them, refluxing and stirring at 110° C. for 6-8 hours, filtering with suction, washing the filter cake, and vacuum drying to obtain material B; S3, take the promoter A, the promoter B, and the deionized water, mix, stir for 20-30min, add the material B, ultrasonically disperse for 30-40min, vacuum dry to constant weight, then carbonize, activate, cool, wash to neutrality, and vacuum dry at 80°C for 10h to obtain the high-purity refined activated carbon; The co-catalyst A is composed of ammonium carbonate and ammonium bisulfite in a mass ratio of 4-5:0.4-0.5; The preparation of the co-catalyst B comprises the following steps: S31, sodium hydride and tetrahydrofuran were mixed, p-hydroxybenzaldehyde was added, the mixture was refluxed at room temperature under nitrogen atmosphere with stirring for 5-7h, hexachlorocyclotriphosphazene was added, the mixture was refluxed at 62-67°C with stirring for 30-40h, filtered, and the liquid phase was taken to obtain material C; S32, take the material C, potassium permanganate, sodium hydroxide, and deionized water, mix them, reflux and stir at 62-67° C. for 30-40 hours, filter, take the liquid phase to adjust the pH to 4-5, filter, take the solid phase and vacuum dry it to constant weight to obtain the co-catalyst B.
2. The process for preparing high-purity refined activated carbon according to claim 1, characterized in that: In step S1, the ratio of the eucalyptus sawdust to the phosphoric acid solution is 10-12 g: 70-80 mL.
3. The process for preparing high-purity refined activated carbon according to claim 1, characterized in that: In step S2, the dosage ratio of material A, diethoxyethyl succinate, deionized water and anhydrous ethanol is 4-5g:10g:40mL:10mL.
4. The process for preparing high-purity refined activated carbon according to claim 1, characterized in that: In step S3, the mass ratio of the co-catalyst A, the co-catalyst B, the deionized water and the material B is 0.1-0.15:0.04-0.05:50:
10.
5. The process for preparing high-purity refined activated carbon according to claim 1, characterized in that: In step S31, the mass ratio of sodium hydride, tetrahydrofuran, p-hydroxybenzaldehyde and hexachlorocyclotriphosphazene is 3-3.3:80-90:9-10:3-4.
6. The process for preparing high-purity refined activated carbon according to claim 1, characterized in that: In step S32, the mass ratio of material C, potassium permanganate, sodium hydroxide and deionized water is 7-8:8-10:2-2.2:300-400.
7. The process for preparing high-purity refined activated carbon according to claim 1, characterized in that: The carbonization refers to heating the temperature to 400-450° C. at a heating rate of 3° C. / min in a nitrogen atmosphere and keeping the temperature for 2-3 hours.
8. The process for preparing high-purity refined activated carbon according to claim 1, characterized in that: The activation refers to heating the temperature to 500-600° C. at a heating rate of 10° C. / min in a nitrogen atmosphere and keeping the temperature for 2-3 hours.
Citation Information
Patent Citations
Nitrogen-doped hierarchical pore carbon and preparation method and application thereof
CN106179440A
Environment-friendly process for preparing activated carbon by virtue of phosphoric acid method
CN108502880A